Pressure and Fluid Effect on Frequency‐Dependent Elastic Moduli in Fully Saturated Tight Sandstone. Issue 11 (18th November 2017) - Yin, Hanjun; Zhao, Jianguo; Tang, Genyang; Zhao, Liming; Ma, Xiaoyi; Wang, Shangxu
Abstract: We developed a system to explore the effects of pressure and fluid viscosity on the dispersion and attenuation of fully saturated tight sandstones, especially at seismic frequencies. Calibration of the new system revealed that the system can operate reliably at frequencies of [2–200, 10 6 ] Hz. Tight sandstone with a "crack–pore" microstructure was tested under nitrogen gas (dry), brine, and glycerin saturation. A frequency‐dependent effect was not found for the dry case. However, apparent dispersion and attenuation for the undrained/unrelaxed transition was clearly observed for sample under brine or glycerin saturation, the magnitude of which was largely suppressed by increasing effective pressure. The measurement results illustrated that increasing the fluid viscosity or the effective pressure will shift the dispersion curve to the lower frequency range. A simple squirt‐flow model with dual‐porosity scheme was used to compare with the measurement results. Although the estimated values deviated slightly from the data, the trend fitted the saturated data relatively well, especially at low effective pressures. Therefore, considering the crack–pore microstructure of the tight sandstone, dispersion and attenuation are induced predominantly by the squirt‐flow stiffening effect from cracks to pores. Key Points: A system for measurement of elastic moduli across a wide frequency band Investigate effects of pressure and fluid viscosity on frequency‐dependent elastic properties of tight sandstone Squirt flow is the dominant mechanism for the dispersion and attenuation at seismic frequency for this tight sandstone